The Influence of Corporate Governance on Sustainability Reporting of Insurance Companies Registered on the IDX - Roswita Savitri; Endang Suhari (International Journal Labs, 2023)
In the contemporary business landscape, prioritizing sustainability is not merely an ethical choice but a strategic imperative for companies seeking long-term viability. Recognizing the multifaceted nature of sustainability, companies engage in sustainability reporting to address the concerns of various stakeholders and to secure their sustained success. This study, conducted over the period 2015-2021, focused on 15 insurance companies, employing a quantitative methodology with purposive sampling. Sustainability reporting, represented by dummy variables, served as the dependent variable, while corporate governance factors such as independent commissioners, gender diversity among commissioners, audit quality, and institutional ownership constituted the independent variables. The empirical analysis, executed using SPSS version 25, yielded nuanced findings. Firstly, the presence of independent commissioners within insurance companies did not exhibit a statistically significant impact on sustainability reporting. Conversely, the inclusion of female independent commissioners displayed a positive correlation with enhanced sustainability reporting. Additionally, the study found that being audited by KAP BIG 4 had no discernible influence on sustainability reporting. However, institutional ownership emerged as a factor significantly affecting sustainability reporting within insurance companies. These research insights contribute to the evolving discourse on corporate sustainability and offer valuable guidance for companies navigating the complex intersection of financial performance and environmental, social, and governance considerations.